Integrating Artificial Intelligence into Social Studies Pedagogy: Opportunities, Challenges and Ethical Considerations - Ossai, Juliet N. (dialektika kontemporer, 2025)
The introduction of artificial intelligence (AI) in the world has come with various kinds of developmental strides. What people cannot deduce at the moment is whether or not these developmental strides are positive or negative. In truism, Artificial Intelligence in Africa in general, and Nigeria in particular, is envisaged as an innovation that can bring about quality, and standard in all sectors including education. As artificial intelligence is gradually being introduced in all sectors of the Nigerian economy, education is one area that needs the exploration of Artificial intelligence especially in teaching and learning. This can be achieved through the integration of AI into the Social Studies pedagogy. Africa’s future is based on its alignment with contemporary and globalized trends. Development in contemporary times has come with the introduction of an innovation referred to as Artificial Intelligence. Artificial Intelligence (AI) is gradually being linked to all aspects of human endeavour including the teaching and learning of Social Studies. Artificial Intelligence (AI) has been current topic of interest and investigation into many fields and subjects including Social Studies. This article investigated integrating artificial intelligence into social studies pedagogy with emphases on opportunities, challenges, and ethical considerations. The study employed a qualitative approach based on a survey of social studies undergraduates in tertiary institutions (TIs) in Delta State. A total of 92 participants were used in the study. The result of the study demonstrates the crucial role of AI in future of Social Studies pedagogy (teaching and learning). The findings highlight the effectiveness and efficiency of AI in equipping Social Studies graduates with new skills for their future career. The findings suggest that AI has positive impact on the learning experience by facilitating the acquisition of new knowledge and skills. This research provides insights into the potential of AI to transform Social Studies pedagogy, and contribute to the development of new skills for Social Studies graduates. It has important implications for educationists, educators, policymakers, and other stakeholders in Social Studies. The study suggests that AI should be more extensively integrated in Social Studies curricula and that tertiary institutions need to consider the opportunities, challenges, and ethical implications of AI in the development, and implementation of Social Studies programmes. By doing so, they can better prepare graduates for the demands of the future workforce in AI era which will by turn, impact on Africa’s future in a globalized society.